Pengaruh Manfaat, Kepercayaan, Kemudahan, Kenyamanan Terhadap Minat Menggunakan Mobile Banking Pada Nasabah Bank Jateng Kantor Cabang Sukoharjo - Alviandra Hikmatiar Wijaya; Banu Witono (ITB AAS Indonesia Surakarta, 2025)
This research aims to analyze the influence of perceived benefits, trust, ease of use, and comfort on the intention to use mobile banking services among customers of Bank Jateng, Sukoharjo Branch. This study employed a quantitative method using a survey approach. The data were collected through a questionnaire distributed to 100 respondents selected using purposive sampling technique. The variables measured in this study include perceived benefits, trust, ease of use, comfort, and intention to use. The data were analyzed using multiple linear regression analysis. The results showed that perceived benefits, trust, ease of use, and comfort had a significant positive effect on the intention to use mobile banking. These findings suggest that improving user perception in these areas may increase the adoption and use of mobile banking services.